The Relationship Between 5-Hydroxytryptamine and Its Metabolite Changes With Post-stroke Depression - Gu, Simeng; He, Zhengming; Xu, Qiuyue; Dong, Jie; Xiao, Tingwei; Liang, Fei; Ma, Xianjun; Wang, Fushun; Huang, Jason H. (Frontiers in Psychiatry, 2022)
Post-stroke depression (PSD) is the most common and serious sequelae of stroke. Approximately 33% of stroke survivors were affected by PSD. However, many issues (incidence, diagnostic marker, risk factor et al) related to PSD remained unclear. The ‘monoamine hypothesis’ is a significant hypothesis for depression, which suggests that three monoamines play a key role in depression. Therefore, most current antidepressants are developed to modulate the monoamines on PSD treatment, and these antidepressants have good effects on PSD patients. However, the potential mechanism of three monoamines in PSD are still unclear. Previously, we proposed “three Primary Emotions” which suggested a new model of basic emotion based on the three monoamines. It may provide a new way for PSD treatment. In addition, recent studies found that monoamine related emotional intervention also showed potential effects in the treatment and prevention of PSD. This review will discuss these issues and attempt to provide a prospect for future research on PSD.